Intensity and distribution in the space-time of the rain erosivity in Goias and Federal District states - Anjos, J. C. R.; Almeida, F. P.; Ferreira, K.; Silva, D. C.; Evangelista, A. W. P.; Alves Júnior, J.; Silva, G. C.; Branquinho, R. G. (Scientific Electronic Archives, 2020)
The ability of rainfall to promote soil disaggregation and transport depends on its intensity and distribution over time, allowing proper soil and water management practices in order to minimize their effects in and outside food production fields. The objective of this study was to verify the intensity of the spatial and temporal distribution of rainfall erosivity in Goias and Federal District states using historical series of rainfall data available at the National Institute of Meteorology (Inmet) from 1986 to 2017. Rainfall erosivity (EI) for Goias and Federal District were estimated using the modified Fournier index. Annual average for factor R were obtained by the sum of the EI in the 12 months of the year. Data were placed to descriptive analysis and classification according to their erosive capacity. The annual mean of the factor R for the study region was 8,834±5.2 MJ mm ha-1 h-1 ano-1, being classified as a strong erosive potential. However, considering the territory, its intensity in Goiás and DF varied from very strong to moderate throughout the year, indicating the need to adopt a conservationist practice that protects the soil from the kinetic energy of rainfall. It is concluded, therefore, that the intensity and distribution of the rainfall erosivity fluctuate both between the municipalities of Goiás (from 4.514±2.5 to 11.215±1.8 MJ mm ha-1 h-1 year-1), and throughout the year (from 180±1.5 to 1.519±4.4 MJ mm ha-1 h-1 month-1).